Dissemination of Covid-19 and Prevention of Its Transmission in Suka Pulung Village - Petrus, Asan; P, Abdul Gafar; Prayugo, Bambang; Hidayat; Pase, M.A (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Since the beginning of 2020 the Covid-19 pandemic has been going on and you don't know when it will end, while the number of cases continues to increase, but there are still many people who have not lived according to health protocols including the people of Suka Pulung village, Langkat Regency, so this activity aims to increase understanding of Covid -19 and efforts to prevent transmission. The method is implemented in the form of a lecture followed by a discussion / question and answer. Results: Based on interviews, questions and answers, observations and pre-test results (mean score of 76.6) and post-test (mean score of 80.5), during the activity, it resulted in an increase in people's understanding of Covid-19. and efforts to prevent its transmission, especially through living according to health protocols, thus there will be no new Covid-19 cluster in the village of Suka Pulung.